CORRELATION BETWEEN LIPID PROFILE AND IMMUNOLOGICAL MARKERS IN POST-COVID PATIENTS WITH DELAYED FRACTURE HEALING - Badriddinov Akobir Sadriddinovich,; Khamdamov Bakhtiyor Zaripovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation The treatment of traumatic injuries with delayed bone consolidation remains a pressing issue due to its severe functional and social consequences. The COVID-19 pandemic has intensified systemic immune and metabolic disturbances that impair osteogenesis. Understanding how lipid disorders correlate with inflammatory and immune markers is crucial for developing targeted therapies. This article provides scientific research information about correlation between lipid profile and immunological markers in post-COVID patients with delayed fracture healing.